Monitoring the activities of sports reserve training institutions on the example of the municipal formation “Yekaterinburg city” - Fitina L.N. ,; Parygin A.V. ,; Khristosova Yu.M. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to study the process of monitoring municipal institutions for training the sports reserve of the municipal formation “Ekaterinburg City”. Methods and structure of the study. The work uses methods of criterion and comparative analysis. The activities of 29 municipal institutions for training sports reserves in 56 sports were analyzed. Results and conclusions. Criteria and tools for monitoring the activities of sports reserve training institutions have been defined. The results of the study can be used by governing bodies in the field of physical culture and sports, and by the management of sports reserve training institutions.